THE YOUNGS MORAL QUALITY FORMING TO USING HISTORIAL INFORMATION - Suleymanova Nodira Inomovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Itʻs article by teachers to pupls and students training history, science educate about history of our population, beloved homeland, and this set up national pride, their amazement and idea conflict global refusing, directions take form streng then immune posted some recommendation.